7a+9b-6b+2a=

Simple and best practice solution for 7a+9b-6b+2a= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7a+9b-6b+2a= equation:


Simplifying
7a + 9b + -6b + 2a = 0

Reorder the terms:
7a + 2a + 9b + -6b = 0

Combine like terms: 7a + 2a = 9a
9a + 9b + -6b = 0

Combine like terms: 9b + -6b = 3b
9a + 3b = 0

Solving
9a + 3b = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-3b' to each side of the equation.
9a + 3b + -3b = 0 + -3b

Combine like terms: 3b + -3b = 0
9a + 0 = 0 + -3b
9a = 0 + -3b
Remove the zero:
9a = -3b

Divide each side by '9'.
a = -0.3333333333b

Simplifying
a = -0.3333333333b

See similar equations:

| -8=6x+x+6 | | -6(4-8z)=22 | | x^2-17x-2280=0 | | (x+5)=(3x-5) | | 5x-2x=y | | 2+a-6=5 | | 4x+3(2+3x)=6+13x | | =330+.8y | | 30x=5x-6 | | 5=3(2p+1)+4(p-2) | | 5(m+8)-m=20 | | 9x+7y-5-4x-12= | | 2u+4=8 | | 3w+15-5-2w=5 | | (-1+2)-2=15 | | 4m+3=5m+7 | | 8K-3K=3K+2 | | R=x+9 | | X-4+8x=6+2x+11 | | -4x=19+13 | | 5x+8=4x-6 | | 7y+14=-4(y+2) | | 9x-5x-x= | | .66(x-3)=11 | | 3z-(-12)=25 | | 10e-3x=7 | | 9k-(2+k)=-(2k+2) | | -x+(-1)=221+2x | | 1-t-2=9(t-8) | | 30-15+2B=45 | | 5/9x-11=-51 | | -2n-3(-8n+7)=-109 |

Equations solver categories